MANFAAT DAUN SALAM DAN DAUN KEMANGI DALAM SEBAGAI ANTIGLIKEMIA, ANTIINFLAMASI DAN ANTIOKSIDAN PADA PENDERITA DM TIPE 2 - Syafriati, Ani (LPPM STIKes Mitra Adiguna, 2025)
Type 2 Diabetes Mellitus (Type 2 DM) is one of the metabolic diseases that is increasingly prevalent and can cause serious complications if not managed properly. Management of Type 2 DM requires a comprehensive approach, including the use of alternative therapies from natural ingredients. Bay leaves (Eugenia polyantha) and basil leaves (Ocimum basilicum) have long been known in traditional medicine for various diseases, including as antidiabetic, anti-inflammatory, and antioxidant agents. This study aims to conduct a systematic review of various studies that discuss the benefits of bay leaves and basil leaves in reducing blood glucose levels (antiglycemia), reducing inflammation (anti-inflammatory), and fighting oxidative damage (antioxidant) in patients with Type 2 DM. Based on the results of the analysis, both leaves showed significant potential in lowering blood glucose levels, inhibiting the inflammatory process, and reducing oxidative stress that plays a role in the pathogenesis of Type 2 DM. However, further research is needed with a stronger design to evaluate the effective dose, mechanism of action, and safety of long-term use. These findings provide supporting evidence for the use of bay leaves and basil leaves as complementary therapies in patients with Type 2 DM.